Consumer ethnocentrism and influence of role model on young female purchase intention towards cosmetics products - Ahmad, Siti Nor Bayaah; Juhdi, Nurita; Jasin, Djasriza; Saidon, Janiffa (The Business Review, 2009)
The study investigates the purchasing behaviour among young female consumers toward cosmetic products. Our paper will discuss the underlying theoretical perspectives that support our proposition and illustrate the various components that might influence the young female behaviour in this particular marketplace. The analysis and investigation is based on cosmetic industry in terms of comparing these young female consumers’ purchase intention of local brand against imported cosmetic brands. The study is taking into consideration two independent variables (influence of role model and ethnocentric tendency) and suggests that differences should exist due to psychological factors.